Adnominal Adjuncts in referentiation sense: a study of recategorization in Phaedrus' fables - Campos Menezes de Moraes, Rachel Maria (2010)
This paper presents a study of adnominal adjuncts in fables Vacca et Capella, Ouis et Leo and Vulpes ad Personam Tragicam, by Phaedrus (sec. I a.D.), in referentiation sense. It relates concepts of adnominal adjuncts and recategorization, as they recategorize and specify the nouns which they refer to. In this way, the referentiation theory, seen as a discursive and cognitive activity, according to Luiz Antônio Marcuschi, Ingedore Koch and others works. Therefore, it was intended to show how adnominal adjuncts recategorize nouns which they refer to, or specify them.